Numerical analysis of load-bearing capacity of modular scaffolding nodes - PieAko, Michal; Blazik-Borowa, Ewa (Engineering structures, 2013)
► Scaffoldings become indispensable during building construction and renovation work. ► The load-bearing capacity of nodes should be determined by numerical methods. ► The local plastic deformation of steel does not mean the total loss of load capacity. ► Nodes are the weakest elements of scaffoldings. The paper is concerned with the numerical analysis of a node in modular scaffolds used for construction work. The purpose of this study is to determine the capacity of a node on the basis of the numerical analysis taking into consideration two factors: nonlinear material and the interaction between particular joint elements. The main subject of the analysis are the connections between the brace and the pipe and between the ledger and the pipe of the vertical standard. The result of the analysis is the maximum load that can be applied to the elements of the node. The numerical analysis is an alternative method over traditional methods involving laboratory research.